2011
DOI: 10.1021/pr100857t
|View full text |Cite
|
Sign up to set email alerts
|

Hexapeptide Libraries for Enhanced Protein PTM Identification and Relative Abundance Profiling in Whole Human Saliva

Abstract: SUMMARY Dynamic range compression (DRC) by hexapeptide libraries increases MS/MS-based identification of lower-abundance proteins in complex mixtures. However, two unanswered questions impede fully realizing DRC’s potential in shotgun proteomics. First, does DRC enhance identification of post-translationally modified proteins? Second, can DRC be incorporated into a workflow enabling relative protein abundance profiling? We sought to answer both questions analyzing human whole saliva. Addressing question one, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 45 publications
3
54
1
Order By: Relevance
“…The latter thus occurs mostly via ionic and hydrogen bonds, bonds that, in turn, are easily challenged by salts, especially positively charged ones such as Tris and free Lys (see Figs. [2][3][4][5]. As a proof of that is the fact that, in the presence of such high levels of adsorption of bile acids and other pigments, the binding of albumin to ProteoMiner is severely quenched.…”
Section: Discussionmentioning
confidence: 99%
“…The latter thus occurs mostly via ionic and hydrogen bonds, bonds that, in turn, are easily challenged by salts, especially positively charged ones such as Tris and free Lys (see Figs. [2][3][4][5]. As a proof of that is the fact that, in the presence of such high levels of adsorption of bile acids and other pigments, the binding of albumin to ProteoMiner is severely quenched.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative protein profiling is also done routinely. Quantitative studies have identified salivary proteins associated with oral cancer 11 , 12 and also systemic conditions such as 2 diabetes 13 and breast cancer 14,15 .…”
Section: Human Protein Products In Whole Salivamentioning
confidence: 99%
“…Post-translation modifications (PTMs), which regulated structure and function of proteins, are possibly the most important aspect of protein biochemistry that can be characterized via MS. In saliva, a number of studies have targeted glycosylation 19,20 , generating a catalog of hundreds of proteins in saliva carrying N-linked glycosylation modifications 21,15 . The phosphoproteome has also been characterized in saliva, with one study identifying phosphorylation events on proline-rich proteins 22 .…”
Section: Human Protein Products In Whole Salivamentioning
confidence: 99%
“…Multiple groups have quantitatively characterized the whole saliva proteome to determine proteins associated with oral cancer 11 , 12 . Others have quantitatively profiled saliva for proteins associated with systemic health conditions, such as type-2 diabetes 13 and breast cancer 14,15 .…”
Section: Intact Proteinsmentioning
confidence: 99%
“…In an extracellular fluid like saliva, glycosylation is a prominent protein PTM, providing critical functions to proteins 19,20 . Several studies have used biochemical enrichment of glycosylated proteins, followed by shotgun MS/MS to catalog these proteins in soluble whole saliva 21,15 resulting in a catalog of hundreds of proteins known to carry glycosylation PTMs.…”
Section: Proteins With Post-translational Modificationsmentioning
confidence: 99%